2021
DOI: 10.3390/app12010170
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Shear-Wave Velocity Structures in Taichung, Taiwan, Using Array Measurements of Microtremors

Abstract: Near-surface S-wave velocity structures (VS) are crucial in site-effect studies and ground-motion simulations or predictions. We explored S-wave velocity structures in Taichung, the second-largest city in Taiwan by population, by employing array measurements of microtremors at a total of 53 sites. First, the fundamental-mode dispersion curves of Rayleigh waves were estimated by adopting the frequency–wavenumber analysis method. Second, the surface-wave inversion technique was used to calculate the S-wave veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The applicability of the microtremor detection method was studied, and a good detection effect was obtained [12]. Huang Huicong et al (2022) carried out microdynamics surveys at 53 sites in Taichung, Taiwan, China, and the results indicated that the thickness of the alluvium decreases from west to east, which is consistent with the geology of the Taichung area [13]. In recent years, microtremor exploration has achieved results in the field of goaf exploration; for instance, Ma Guosong (2022) applied the microtremor method to the exploration of a water-rich goaf for the first time.…”
Section: Introductionmentioning
confidence: 88%
“…The applicability of the microtremor detection method was studied, and a good detection effect was obtained [12]. Huang Huicong et al (2022) carried out microdynamics surveys at 53 sites in Taichung, Taiwan, China, and the results indicated that the thickness of the alluvium decreases from west to east, which is consistent with the geology of the Taichung area [13]. In recent years, microtremor exploration has achieved results in the field of goaf exploration; for instance, Ma Guosong (2022) applied the microtremor method to the exploration of a water-rich goaf for the first time.…”
Section: Introductionmentioning
confidence: 88%